Manajemen Pengelolaan Surat dan Pengarsipan Surat di MAS Al-Washliyah Galang Kota - Tengku Darmansah; Dini Sholeha; Aidelia Nova Liza; Dimas Dwika Syahramanda; Malika Aulia Husnah; Siti Arafah Effendi (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to find out how letters are managed and archived at MAS Al-Washliyah Galang. The research introduction explains the importance of letter management and archiving in increasing the effectiveness of correspondence management. The research method used is qualitative with a literature study approach, which involves analysis of various related literature. The aim of the research is to understand how letters are managed, letter archiving management and procedures for managing and archiving incoming letters at school. The research findings show that good management and archiving of letters has a big impact on schools and the management and archiving of letters makes them more effective and efficient. However, management and archiving must also go through several procedures so that it runs well. In conclusion, the management and archiving of letters has a very positive impact on schools because it greatly reduces the effort for teaching staff and makes it easier, but requires going through several procedures in managing it.